2015
DOI: 10.4141/cjss-2014-012
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on nutrient losses from the Pike River watershed of southern Québec

Abstract: . 2015. Impacts of climate change on nutrient losses from the Pike River watershed of southern Que´bec. Can. J. Soil Sci. 95: 337Á358. The impacts of climate change on water quality in the Pike River watershed, an important contributor of nutrient loads into the northern arm of Lake Champlain, were simulated for the time horizon 2041Á2070. Four water quality scenarios were simulated using a calibrated version of the Soil and Water Assessment Tool (SWAT) customized to Que´bec agroclimatic conditions. Three of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Spring and summer months are projected to have lower streamflow and nitrogen export, while winter and fall months are expected to have higher streamflow and nitrogen export. A similar seasonal change in streamflow and nitrogen export due to climate change was found for Pike River watershed in southern Quebec that has similar land use, soil, and climate characteristics to our study watershed [18].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Spring and summer months are projected to have lower streamflow and nitrogen export, while winter and fall months are expected to have higher streamflow and nitrogen export. A similar seasonal change in streamflow and nitrogen export due to climate change was found for Pike River watershed in southern Quebec that has similar land use, soil, and climate characteristics to our study watershed [18].…”
Section: Discussionsupporting
confidence: 83%
“…For both A2 and B1 scenarios, the decreases are mainly in spring and summer months by −35.5% (−17.8 to −48.7%) and the increases are in fall and winter months by 50.8% (10.7 to 107.8%) by the end century (Table 4). Similar studies that were conducted in the Pike River watershed in southern Quebec [18] and the Eagle Creek Watershed in Indiana [21] using SWAT also predicted that nitrogen load would increase in winter and decrease in summer due to climate change. ; from eight GCMs predicted B1 emission scenarios at EPA station J0770000; and, (d) the average inorganic nitrogen loading over the eight GCMs for the three study periods.…”
Section: Projected Changes In Nitrogen Transportmentioning
confidence: 56%
See 1 more Smart Citation
“…In a study using SWAT model, [70], found that annual P loading would decrease in the future from a watershed in Lake Erie basin due to increased evapotranspiration and decreased snowfall. On the other hand, [14,18,19,68,71,72] all found that nutrient losses may increase in future in Ontario and Quebec watersheds.…”
Section: Effects Of Climate Change On Tile Discharge and Nitrogen Yieldsmentioning
confidence: 99%
“…Nearly all studies have shown that climate change is likely to have a significant impact on contaminants' loads. Most indicate an overall increase in contaminants loads [8][9][10][11][12][13][14][15][16]. It is obvious that this increase corresponds to water flow augmentation driven by precipitation increase.…”
Section: Introductionmentioning
confidence: 99%